2008
DOI: 10.1162/leon.2008.41.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Leonardo da Vinci: A Review

Abstract: The article reviews scholarship on Leonardo da Vinci during the 20th century. An initial fascination with a handful of paintings has led to a nearly comprehensive understanding of his art. A catalogue raisonnée for Leonardo and his school has yet to be made. Awareness of Leonardo as a scientist began with a vague reputation of a universal genius who never finished anything. Some praised, others sought to limit him as an artist-engineer. The 20th century revealed that Leonardo made substantial contributions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A friend of Leonardo once remarked that the artist's "mathematical explorations hindered him from concentrating on painting to the point where he could no longer tolerate his brushes" at that particular time in his life. In order for future painters to create their work in an even more precise and perfect manner, Leonardo da Vinci played a key part in laying the groundwork for the foundations connecting arithmetic and geometry to art [8].…”
Section: Influence On Modern Societymentioning
confidence: 99%
“…A friend of Leonardo once remarked that the artist's "mathematical explorations hindered him from concentrating on painting to the point where he could no longer tolerate his brushes" at that particular time in his life. In order for future painters to create their work in an even more precise and perfect manner, Leonardo da Vinci played a key part in laying the groundwork for the foundations connecting arithmetic and geometry to art [8].…”
Section: Influence On Modern Societymentioning
confidence: 99%
“…He also employed numerous abbreviations and contractions, with no punctuation, and wrote in his native Florentine at a time when Italian spelling and grammar forms were far from standardized. 2 It has been suggested that the more than 6000 pages now known to us may perhaps represent only half, or even a quarter or less of his total output, the rest having been lost [2,3,4]. Over time, many of these separate sheets have been rearranged, rebound and even in some cases dissected into smaller pieces [5].…”
Section: The Notebooksmentioning
confidence: 99%
“…There are also a few relevant sheets in the Royal Collection at Windsor Castle 18/04/2016 (Windsor). Pages are conventionally referred to by the number of the folio (leaf) followed by the letter 'r' (recto) or 'v' (verso) 4 .…”
Section: The Notebooksmentioning
confidence: 99%
“…This was provided 300 years after Leonardo by Wheatstone's stereoscope'' (Wade, Ono, and Lillakas 2001, 231). Kim Veltman (2007) writes, ''After 1500, his major paintings can be seen as attempts to address one fundamental challenge: how to create effects of three-dimensional relief under carefully controlled conditions. Speaking anachronistically, he was trying to create auto-stereoscopic effects in paintings.…”
Section: Visual Punmentioning
confidence: 99%